The prevalence of left and right bundle branch block morphology ventricular tachycardia amongst patients with arrhythmogenic cardiomyopathy and sustained ventricular tachycardia: insights from the European Survey on Arrhythmogenic Cardiomyopathy. Issue 2 (7th September 2021) - Belhassen, Bernard; Laredo, Mikael; Roudijk, Rob W; Peretto, Giovanni; Zahavi, Guy; Sen-Chowdhry, Srijita; Badenco, Nicolas; Te Riele, Anneline S J M; Sala, Simone; Duthoit, Guillaume; van Tintelen, J Peter; Paglino, Gabriele; et al.
Abstract: Aims: In arrhythmogenic cardiomyopathy (ACM), sustained ventricular tachycardia (VT) typically displays a left bundle branch block (LBBB) morphology while a right bundle branch block (RBBB) morphology is rare. The present study assesses the VT morphology in ACM patients with sustained VT and their clinical and genetic characteristics. Methods and results: Twenty-six centres from 11 European countries provided information on 954 ACM patients who had ≥1 episode of sustained VT spontaneously documented during patients' clinical course. Arrhythmogenic cardiomyopathy was defined according to the 2010 Task Force Criteria, and VT morphology according to the QRS pattern in V1. Overall, 882 (92.5%) patients displayed LBBB-VT alone and 72 (7.5%) RBBB-VT [alone in 42 (4.4%) or in combination with LBBB-VT in 30 (3.1%)]. Male sex prevalence was 79.3%, 88.1%, and 56.7% in the LBBB-VT, RBBB-VT, and LBBB + RBBB-VT groups, respectively ( P  = 0.007). First RBBB-VT occurred 5 years after the first LBBB-VT (46.5 ± 14.4 vs 41.1 ± 15.8 years, P  = 0.011). An implanted cardioverter-defibrillator was more frequently implanted in the RBBB-VT (92.9%) and the LBBB + RBBB-VT groups (90%) than in the LBBB-VT group (68.1%) ( P  < 0.001). Mutations in PKP2 predominated in the LBBB-VT (65.2%) and the LBBB + RBBB-VT (41.7%) groups while DSP mutations predominated in the RBBB-VT group (45.5%). By multivariable analysis, female sex was associated with LBBB + RBBB-VT ( P  = 0.011) while DSP mutations were associated with RBBB-VT ( P  < 0.001). After a median follow-up of 103 (51–185) months, death occurred in 106 (11.1%) patients with no intergroup difference ( P  = 0.176). Conclusion: RBBB-VT accounts for a significant proportion of sustained VTs in ACM. Sex and type of pathogenic mutations were associated with VT type, female sex with LBBB + RBBB-VT, and DSP mutation with RBBB-VT. Graphical Abstract: